DUX4r, ZNF384r and PAX5-P80R mutated B-cell precursor acute lymphoblastic leukemia frequently undergo monocytic switch - Novakova, Michaela (Haematologica, 2020)
Recently, we described B-cell precursor acute lymphoblastic leukemia (BCP-ALL) subtype with an early switch to the monocytic lineage and the loss of the B-cell immunophenotype, including CD19 expression. Thus far, the genetic background has remained unknown. Among 726 children consecutively diagnosed with BCP-ALL, 8% patients experienced a switch detectable by flow cytometry (FC). Using exome and RNA sequencing, the switch was found to positively correlate with three different genetic subtypes: PAX5-P80R mutation (five cases with switch of five), rearranged (DUX4r) (30 cases of 41) and rearranged (ZNF384r) (four cases of ten). Expression profiles or phenotypic patterns correlated with genotypes, but within each genotype no cases who subsequently switched could be indentified. If switching was not taken into account, the B-cell-oriented FC assessment underestimated the minimal residual disease level. For patients with PAX5-P80R, a discordance between FC-determined and polymerase chain reactiondetermined minimal residual disease was found on day 15, resulting from a rapid loss of the B-cell phenotype. Discordance on day 33 was observed in all the DUX4r, PAX5-P80R and ZNF384r subtypes. Importantly, despite the substantial phenotypic changes, possibly even challenging the appropriateness of BCP-ALL therapy, the monocytic switch was not associated with a higher incidence of relapse and poorer prognosis in patients undergoing standard ALL treatment.